Investigation into different numerical methods in predicting the response of aluminosilicate glass under quasi-static and impact loading conditions. (15th April 2021) - Wang, Zhen; Ma, Dayou; Suo, Tao; Li, Yulong; Manes, Andrea
Highlights: Numerical approaches for modeling brittle materials in both quasi-static and dynamic loading conditions are considered. Finite Element Method coupled to Smooth Particle Hydrodynamics (FEM-SPH), Discrete Element Method (DEM) and the elastic bond-based Peridynamics (PD). The mechanical behavior of aluminosilicate glass, were calibrated for each numerical model by means of experimental tests on material coupons. Quasi-static three-point bending tests and ballistic impact tests were utilized for numerical models' assessment. FEM-SPH is the most capable in modelling the material strength, projectile velocity and failure morphology Abstract: This paper presents a comparison of three numerical approaches for modeling brittle materials in both quasi-static and dynamic loading conditions. These methods include the Finite Element Method coupled to Smooth Particle Hydrodynamics (FEM-SPH), Discrete Element Method (DEM) and the elastic bond-based Peridynamics (PD). Numerical models for each method were built in the commercial software LS-DYNA. The parameters, associated to the mechanical behavior of aluminosilicate glass, were calibrated for each numerical model by means of experimental tests on material coupons. The experimental results from quasi-static three-point bending tests and ballistic impact tests were utilized for numerical models' assessment. All methods provide comparable results under quasi-static flexural loading condition and for ballistic impact cases, the numerical results show the particular capability of each approach to capture the projectile residual velocity and the damage morphology of aluminosilicate glass tiles. However, considering all the loading conditions the FEM-SPH method replicates the mechanical response of aluminosilicate glass best. Graphical abstract: Image, graphical abstract